Factors Determining Nephrotoxicity and Mortality in Critical Care Patients Receiving Colistin - Ciftci, Ali; Izdes, Seval; Altintas, Neriman Defne (The Journal of Infection in Developing Countries, 2018)
Introduction: We aimed to determine risk factors for nephrotoxicity and factors affecting mortality in patients who received colistin. Methodology: Critical patients who received colistin were enrolled. Pregnancy, age < 18 years, basal creatinine level > 2 mg/dL, colistin use for < 48 hours, and previous renal replacement therapy were exclusion criteria. KDIGO stages were determined according to creatinine levels. Patients were grouped as those with no acute kidney injury (Group N0) and those with acute kidney injury (Group N). Their demographic data, APACHE II and SOFA scores, treatments, and laboratory results were recorded. Results: A total of 91 patients were included: 27 in Group N0 and 64 in Group N. Demographic data were similar between groups; however, higher admission APACHE-II scores (OR:1.179, 95% CI:1.033-1.346, p = 0.015) and need for vasopressors (OR:5.486, 95% CI:1.522–19.769, p = 0.009) were found to be independent risk factors for nephrotoxicity. Higher APACHE II scores (OR:1.253, %95 CI:1.093-1.437, p = 0.001), presence of coronary artery disease (OR:7.720, % 95 CI: 1.613-36.956, p = 0.011), need for vasopressors (OR: 4.587, % 95 CI: 1.224 – 17.241, p = 0.024), hypoalbuminemia (OR: 4.721, % 95 CI: 1.088 – 20.469, p = 0.038), and higher direct bilirubin levels (OR: 1.806, % 95 CI: 1.055 – 3.092, p = 0.031) were independent risk factors for mortality. Conclusion: When use of colistin is considered in ICU patients, presence of modifiable risk factors for nephrotoxicity such as hypoalbuminemia, nephrotoxic drug administration, and presence of shock should be determined and managed to prevent nephrotoxicity.